Acute pericardial tamponade complicating spinal surgery in a child with Duchenne muscular dystrophy. - Watkin, N; Ostman-Smith, I; Padgett, L; Fairbank, J (1993)
A hitherto unrecognised problem of pericardial tamponade complicating spinal surgery in a child with Duchenne muscular dystrophy is reported in this paper.